RELIGIOSITY IN ART INSPIRED BY SAMUAN TIGA AND TEJAKULA, BALI: UNITY IN DIVERSITY - Butler, Diane Carol; Ardika, I Wayan; Sedyawati, Edi; Parimartha, I Gde (E-Journal of Cultural Studies; Vol. 5, No. 2 Juli 2011, 2012)
At the dawn of this third millennium, growing numbers of forums worldwide are focused on the issue of how to sustain the diversity of the nature and of cultures for the well-being of the Earth and humanity. Concurrently, intercultural and interreligious dialogue is deemed essential for social cohesion. This dissertation advances the contributions of religiosity in art through a qualitative reflective account and chronicle of the art and dialogues offered by people of diverse cultures and faiths from 1999 to 2004 during Sharing Art & Religiosity in the vicinity of Pura Samuan Tiga in Bedulu, Bali and Sharing Art Ocean– Mountain at  the  seacoast village of Tejakula, North  Bali;  seen in  tandem  with creative transformations that occurred through Sharing Art in and with other cultural environments of the world. Methodologically this study stemmed from and demonstrates the merits of public participatory   practice-based   art   programs   whereby   activities   are   conceived   by   and implemented with the people of a locale. Participants generated the data and interpretations via mutual cooperation, dialogue, and creative praxis. The Balinese principle of Tri Hita Karana, that aims toward a harmonious human-nature-God/Source of Life relationship in accord with the place-time-conditions, provided a holistic perspective to analyze and derive meaning from the results. Findings indicate sharing in the arts, religiosity, and nature fosters a common field such that traditional and modern cultures can study and engage in creative dialogue together. Moreover, interreligious innovations that have continued to develop since the seminal deliberation  of  reconciliation  between  Bali  Aga,  Çiwaist,  and  Buddhist  faith  groups  at Samuan Tiga circa CE 989 to 1011 and intercultural egalitarian innovations since the seventeenth century dialogue of indigenous and migrant mountain and maritime cultures in Tejakula – constitute a model for furthering bhinneka tunggal ika unity in diversity in the world today. Recommendations outline how the findings can be used for cooperative exchanges between villages and between villages and cities of diverse regions and countries to support interculture in cultural environments. Appendices provide two video compact discs; seventy- nine  reflective  essays  by artists,  religious/spiritual leaders,  scholars,  and  educators  from across the world; and nine transcriptions of initial public dialogues.
Keywords: religiosity in art; local genius; intercultural and interreligious creativity; interculture in cultural environments; tri hita karana; unity in diversity; bhinneka tunggal ika; Samuan Tiga; Tejakula; Bali; Indones